When and how vicarious abusive supervision leads to bystanders' supervisor-directed deviance: A moderated–mediation model. Issue 7 (4th November 2019) - Chen, Shu-Chen; Liu, Na-Ting
Abstract : Purpose: The purpose of this paper is to examine bystanders' supervisor-directed deviance to vicarious abusive supervision by supervisor-directed attribution. Furthermore, this study developed a moderated–mediation model to explore how LMX between bystander and his/her supervisor moderate the relationship between vicarious abusive supervision and the supervisor-directed attribution, which subsequently influences bystanders' supervisor-directed deviance. Design/methodology/approach: The paper tested the model using a sample of 336 workers using a two-wave survey. A moderated–mediation analysis was conducted with bootstrapping procedure to test the first stage moderated–mediation model in this study. Findings: The results showed that LMX (between bystander and his/her supervisor) weakens the indirect relationship between vicarious abusive supervision and supervisor-directed deviance by bystanders' supervisor-directed attribution. Practical implications: Leadership training programs should be conducted to caution supervisors in terms of the deleterious consequences of vicarious abusive supervision. Organizations also should plan perception and communication training courses for leaders; such training would reduce bystanders' responsibility attribution to them by providing timely explanations and communication. Furthermore, organizations should monitor supervisors by managers' performance appraisal and formulate rules to punish abusive managers. Originality/value: These results clarify the nature and consequences of LMX (dyadic relationships of bystanders–supervisor) for bystanders' attribution process, and explain underlying attributional perceptions and reactions to vicarious abusive supervision. This study provides a more nuanced understanding of when and how vicarious abusive supervision leads to bystanders' supervisor-directed deviance.